2003
DOI: 10.1093/emboj/cdg115
|View full text |Cite
|
Sign up to set email alerts
|

HDAC-6 interacts with and deacetylates tubulin and microtubules in vivo

Abstract: Microtubules are cylindrical cytoskeletal structures found in almost all eukaryotic cell types which are involved in a great variety of cellular processes. Reversible acetylation on the ϵ‐amino group of α‐tubulin Lys40 marks stabilized microtubule structures and may contribute to regulating microtubule dynamics. Yet, the enzymes catalysing this acetylation/deacetylation have remained unidentified until recently. Here we report that β‐tubulin interacts with histone deacetylase‐6 (HDAC‐6) in a yeast two‐hybrid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
579
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 660 publications
(612 citation statements)
references
References 38 publications
22
579
1
3
Order By: Relevance
“…We evaluated the acetylation status in A2780 ovarian carcinoma cells of H3, which is acetylated through class I HDACs (Glaser et al, 2003), and tubulin, which is acetylated by the class II family member HDAC6 (Matsuyama et al, 2002;Zhang et al, 2003). Inhibition of HDAC6 also induces Hsp90 acetylation, resulting in Hsp70 induction and degradation of Hsp90-associated pro-survival and pro-proliferative client proteins such as c-raf (Bali et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the acetylation status in A2780 ovarian carcinoma cells of H3, which is acetylated through class I HDACs (Glaser et al, 2003), and tubulin, which is acetylated by the class II family member HDAC6 (Matsuyama et al, 2002;Zhang et al, 2003). Inhibition of HDAC6 also induces Hsp90 acetylation, resulting in Hsp70 induction and degradation of Hsp90-associated pro-survival and pro-proliferative client proteins such as c-raf (Bali et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, class IIa enzymatic activity is not intrinsic, but derived from its association with HDAC3 (Fischle et al, 2002). Inhibition of the class IIb enzyme HDAC6, which is a tubulin and Hsp90 deacetylase, caused a-tubulin hyperacetylation and decreased cell motility, but did not affect cell-cycle progression Zhang et al, 2003). Although inhibition of class II HDAC enzymes does not result in antiproliferative activity in vitro, it may potentiate antitumoral effects of other anticancer agents such as radiation (through HDAC4) or proteasome inhibitors (through HDAC6) (Bali et al, 2005).…”
mentioning
confidence: 99%
“…The first attempt showed that each domain possessed an independent catalytic activity (Grozinger et al, 1999). This result was, however, challenged by other groups showing that the HDAC activity of HDAC6 relies either on the integrity of both HDAC domains (Zhang et al, 2003 or is mediated by its second catalytic domain (Zou et al, 2006). The discovery of a-tubulin as an HDAC6 substrate (Hubbert et al, 2002;Matsuyama et al, 2002;Zhang et al, 2003) allowed researchers to also include acetylated tubulin in these assays (Haggarty et al, 2003;Zhang et al, 2003Zhang et al, , 2006Zou et al, 2006).…”
Section: Domain Organization and Structural Features Of Hdac6mentioning
confidence: 99%
“…The discovery of a-tubulin as an HDAC6 substrate (Hubbert et al, 2002;Matsuyama et al, 2002;Zhang et al, 2003) allowed researchers to also include acetylated tubulin in these assays (Haggarty et al, 2003;Zhang et al, 2003Zhang et al, , 2006Zou et al, 2006). Here again, some of the investigators found that the integrity of both HDAC6 catalytic domains was indispensable for the whole tubulin deacetylase (TDAC) activity of the enzyme (Zhang et al, 2003, whereas others showed that the whole TDAC activity could be attributed to the second domain (Haggarty et al, 2003;Zou et al, 2006).…”
Section: Domain Organization and Structural Features Of Hdac6mentioning
confidence: 99%
See 1 more Smart Citation